INQUIRY - CHART FOR TEACHING CRITICAL READING - Okitasari, Indah (IKIP Siliwangi, 2022)
This study aims to investigate how inquiry chart facilitates students in learning critical reading and to describe benefits and challenges found by students during teaching and learning process. Qualitative research data were collected through classroom observation, written test and depth interview. The results revealed that I-Chart learning strategy facilitated students to learn critical reading abilities. Deep interview confirmed that students responded positively toward the I-Chart learning strategies. They were motivated to learn and read more texts. They admitted that the learning strategies might have been the tool for them to enhance deep knowledge of a topic. However, the study found that students remained inactive in delivering arguments in the classroom. Students’ background knowledge had been one of the teaching obstacles found in this study. Time constraints and unavailability of internet access might be the serious problem to encounter in the process of teaching and learning in the classroom. More participants are recommended for further research. Keywords: Inquiry-Chart, Reading